NEW FUNCTION

Function Expression :

\[f(x)=\frac{1}{(x+1 )(x+2 )} \]

Domain

\[\left]-\infty, -2\right[ \cup \left]-2, -1\right[ \cup \left]-1, \infty\right[ \]

Limits

\[\lim_{x \rightarrow-\infty}f(x) = 0 \]
\[\lim_{x \overset{<}{\rightarrow-2} }f(x) = +\infty \]
\[\lim_{x \overset{>}{\rightarrow-2} }f(x) = -\infty \]
\[\lim_{x \overset{<}{\rightarrow-1} }f(x) = -\infty \]
\[\lim_{x \overset{>}{\rightarrow-1} }f(x) = +\infty \]
\[\lim_{x \rightarrow+\infty}f(x) = 0 \]
\[ \]

Derivate

\[f^{\,\prime}(x)=\frac{\frac{1}{\left(x + 1\right) \left(x + 2\right)} \left(- 2 x - 3\right)}{\left(x + 1\right) \left(x + 2\right)} \]
\[f^{\,\prime}(x)=\frac{- 2 x - 3}{\left(x + 1\right)^{2} \left(x + 2\right)^{2}} \]
\[ \]

Integral

\[F(x) = \log{\left(x + 1 \right)} - \log{\left(x + 2 \right)} \]

Sign Table


Variation Table


Plot


Elapsed Time: 0.0849 seconds